Динамічна магнітна система сфероїд - вільний диполь та її Maple-моделювання - Козоріз, В.В.; Козоріз, О.В.; Ляшко, С.І. (Видавничий дім "Академперіодика" НАН України, 2007)
A solution of the Cauchy problem and phase portraits based on Maple-software procedures for a system of non-linear differential equations of the 12-th order describing the free magnetic dipole dynamics in the field of an immobile elongated spheroidal permanent magnet are derived.